Macrophage activation syndrome and COVID-19 - Ryo Otsuka; Ken-ichiro Seino (BMC, 2020)
Abstract An emerging, rapidly spreading coronavirus SARS-CoV-2 is causing a devastating pandemic. As we have not developed curative medicine and effective vaccine, the end of this life-threatening infectious disease is still unclear. Severe COVID-19 is often associated with hypercytokinemia, which is typically found in macrophage activation syndrome. SARS-CoV-2 infection causes this strong inflammation within the lung and propagates to respiratory and, ultimately, systemic organ malfunction. Although we have not fully understood the physiological and pathological aspects of COVID-19, current research progress indicates the effectiveness of anti-cytokine therapy. Here, we summarize macrophage activation syndrome and its possible contribution to COVID-19, and cytokine targeted attempts in severe COVID-19 cases.